Integrating literature and family insights: exploring the needs of families supporting adults with diabetes - Vânia Lídia Soares; Vânia Lídia Soares; Sara Lemos; Sara Lemos; Carlos Sequeira; Carlos Sequeira; Carminda Soares Morais; Carminda Soares Morais; Carminda Soares Morais; Maria do Céu Barbieri-Figueiredo; Maria do Céu Barbieri-Figueiredo; Maria do Céu Barbieri-Figueiredo (Frontiers in Public Health)
IntroductionThe considerable influence that family members can have on diabetes management is well recognized. Therefore, it is crucial for professionals to acknowledge the impact of the diagnosis on family members. This study aimed to comprehensively identify and understand the needs of family members with an adult diagnosed with diabetes using a two-phased research design.MethodsPhase 1 was a scoping literature review using databases such as MEDLINE®, CINAHL®, SciELO, and PsycINFO, and gray literature from the Scientific Open Access Repository of Portugal and OpenGrey, focusing on studies from 2017 to 2023, adhering to the Joanna Briggs Institute and PRISMA guidelines. Phase 2 involved a focus group to gather qualitative data on family experiences, which was analyzed using content analysis and following the Consolidated Criteria for Reporting Qualitative Research.Results from both phases revealed five themesCommunication and emotional expression within families, the impact of diabetes on the family, diabetes-specific knowledge, socio-cultural and environmental influences on diabetes management, and communication with healthcare providers. Integrating these findings highlighted the specific needs of families, suggesting that tailored interventions should be developed to enhance diabetes management support and promote overall family well-being.